Tra poesia e psicoanalisi Note sull’opera di Durs Grünbein (ENTHYMEMA, 2019)
Between Corporeal Turn and biocognitive models, poetry and psychoanalysis do not cease to draw attention to the crucial importance of language in order to show that human knowledge is overdetermined with phantasmatic dimensions, which do express themselves in words, rythm and rhetorical strategies. Poetry and psychoanalysis transgress the limits of selfconscious communication and grow in complexity and alternative modes of expression by showing deep distrust in naming, conceptualising and defining, thus enhancing a knowledge which obviates mastery. This account of the inextricability of psychoanalysis and poetry is worked out in a reading of the lyrical and essaystic production of Durs Grünbein, one of the most eminent contemporary German poets. The works of the poet, who spent more than 20 years in East-Germany, where he was born, explore the creative processes that preside over poetic production and emerge in everyday life, whenever the individual breaks free from the imposition of preconceived categories thwarting human emotions and feelings. Focusing upon the creative potentialities at stake in unconscious processes, Grünbein investigates the fragmentariness of our world, the fragility and precariousness of life in order to represent the impingement of “Being” on prosodic and stylistic features inspired by poetic objects, whose shapes and motion of words on the page can be compared with the internalised objects of psychoanalysis. Freud’s concept of Bahnung will also act as a beacon for navigating the creative strategies developed by Grünbein’s production in coping with internal objects and projective identifications.
Keywords: Durs Grünbein; poetry; psychoanalysis; analytical object; poetic object; creative processes; Freud; Bahnung